(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article deals with the training of learners for family life, psychological, ethnicfeatures of the problem, skills of family relationship and aboutin the formation of family life inadolescents, taking into account our nationality, national and family values